Linguistic Analysis behind Innovative Renderings of ʾiysh‎ in a Newly Published Translation - Stein, David E. 1957- (2024)
The Revised Jewish Publication Society translation of the Hebrew Bible (RJPS, 2023), an adaptation of the meaning-based English version known as NJPS (1985, 1999), has changed many renderings of the personal noun אִישׁ‎ (usually glossed as “man; person”). This article explains the cognitively based, communication-oriented thinking behind seventy new renderings. In these cases, singular אִישׁ‎ appears in construct with a group name (most often יִשְׂרָאֵל‎ “Israel”) and refers to a specific plurality of persons regarded as a single body. The analysis views אִישׁ‎ as a situating noun, that is, its use profiles its referent in terms of the depicted situation. The proposed motivation for singular collective usage is to make a pragmatic contrast with אֲנָשִׁים‎ (the standard plural of אִישׁ‎) to situate the participant in the bigger picture. This situation-oriented approach readily yields coherent and informative texts while solving interpretive cruxes. Principles for translating a situating noun are also briefly discussed.
Keywords: situating nouns; RJPS translation; pragmatic contrast; plain sense; grammatical number; collective nouns; Cognitive Linguistics; Biblical Hebrew; אִישׁ‎